DESIGNING WEB-BASED LIBRARY APPLICATIONS AT ATTAUFIQIYYAH JUNIOR HIGH SCHOOL USING THE CODEIGNITER FRAMEWORK - Sunardi, Sunardi; Permana, Basuki Rakhim Setya (Nindikayla Institute, 2023)
In the design of this library application, the programming language used is the web-based programming language, PHP, utilizing the Code Igniter Framework. The database employed in the design of this library application is MySQL. The aim of this research is to develop and design a Library Application and determine the system's feasibility by users at SMP Attaufiqiyyah. The method utilized in this research is the PIECES method (Performance, Information, Economic, Control, Efficiency, and Service). The results of this research illustrate that with a computerized library application, the staff no longer need to manually write book and member data, as well as borrowing transactions. They no longer have to search for book data on shelves and book stacks, simplifying the book search process for students. The conclusion is that with an online library system, the staff no longer need to manually record borrowing and returning data. With this library system, the staff no longer need to doublecheck book data. This system facilitates staff in conducting transactions from borrowing to returning books and handling fines